Analyzing individuals' grip force over short intervals in a joystick-controlled task with and without a stress manipulation. Issue 5 (4th April 2021) - Botzer, Assaf; Sahar, Yotam; Wagner, Michael; Elbaum, Tomer
ABSTRACT: The current experiment is part of an ongoing feasibility testing of grip force as a measure of stress in joystick-controlled tasks. In a previous study, we showed that grip force of one group was higher under a stress manipulation, and higher than of another group without stress manipulation. In the current experiment, we tested if we could identify greater grip force under stress, per individual. Fourteen participants performed tracking tasks in trials with and without a stress manipulation. We computed the mean grip force of each participant in several intervals to test how soon (if at all) his grip force in the trials with the stress manipulation had become significantly higher than in the trials without the stress manipulation. In ∼31% of the comparisons, we were able to detect higher grip force with than without the stress manipulation after 5 s through the trials. Other detections of greater grip force took longer, but no longer than 30 s. However, not all participants gripped significantly harder during the stress manipulation. The current experiment added support to the feasibility of using grip force as a measure of stress in joystick-controlled tasks and pointed to the next necessary steps in evaluating its feasibility.